Morphology engineering for novel antibiotics: Effect of glass microparticles and soy lecithin on rebeccamycin production and cellular morphology of filamentous actinomycete Lentzea aerocolonigenes - Dinius, Anna; Schrinner, Kathrin; Schrader, Marcel; Kozanecka, Zuzanna Justyna; Brauns, Henry; Klose, Leon; Weiß, Hannah; Kwade, Arno; Krull, Rainer (Frontiers in Bioengineering and Biotechnology, 2023)
Lentzeaaerocolonigenes, as an actinomycete, is a natural producer of the antibiotic and antitumoral drug rebeccamycin. Due to the filamentous cellular morphology handling in cultivations is challenging; therefore, morphology engineering techniques are mandatory to enhance productivity. One promising approach described in the literature is the addition of mineral particles in the micrometer range to precisely adjust cellular morphology and the corresponding product synthesis (microparticle-enhanced cultivation, MPEC). Glass microparticles are introduced in this study as a novel supplementation type for bioprocess intensification in filamentous organisms. Several investigations were conducted to screen for an optimal particle setup, including particle size and concentration regarding their impact and effects on enhanced productivity, microparticle incorporation behavior into the biopellets, the viability of pellets, and morphological changes. Glass microparticles (10 g·L−1) with a median diameter of 7.9 µm, for instance, induced an up to fourfold increase in product synthesis accompanied by overall enhanced viability of biomass. Furthermore, structural elucidations showed that biopellets isolated from MPEC tend to have lower hyphal density than unsupplemented control pellets. In this context, oxygen microprofiling was conducted to better understand how internal structural changes interwind with oxygen supply into the pellets. Here, the resulting oxygen profiles are of a contradictive trend of steeper oxygen consumption with increasing glass microparticle supplementation. Eventually, MPEC was combined with another promising cultivation strategy, the supplementation of soy lecithin (7.5 g·L−1), to further increase the cultivation performance. A combination of both techniques in an optimized setup resulted in a rebeccamycin concentration of 213 mg·L−1 after 10 days of cultivation, the highest value published so far for microparticle-supplemented shake flask cultivations of L. aerocolonigenes.